Sports-Related Concussions in Youth: Improving the Science, Changing the Culture - Institute of Medicine; National Research Council (The National Academies Press, 2014)
In the past decade, few subjects at the intersection of medicine and sports have generated as much public interest as sports-related concussions - especially among youth. Despite growing awareness of sports-related concussions and campaigns to educate athletes, coaches, physicians, and parents of young athletes about concussion recognition and management, confusion and controversy persist in many areas. Currently, diagnosis is based primarily on the symptoms reported by the individual rather than on objective diagnostic markers, and there is little empirical evidence for the optimal degree and duration of physical rest needed to promote recovery or the best timing and approach for returning to full physical activity. Sports-Related Concussions in Youth: Improving the Science, Changing the Culture reviews the science of sports-related concussions in youth from elementary school through young adulthood, as well as in military personnel and their dependents. This report recommends actions that can be taken by a range of audiences - including research funding agencies, legislatures, state and school superintendents and athletic directors, military organizations, and equipment manufacturers, as well as youth who participate in sports and their parents - to improve what is known about concussions and to reduce their occurrence. Sports-Related Concussions in Youth finds that while some studies provide useful information, much remains unknown about the extent of concussions in youth; how to diagnose, manage, and prevent concussions; and the short- and long-term consequences of concussions as well as repetitive head impacts that do not result in concussion symptoms. The culture of sports negatively influences athletes' self-reporting of concussion symptoms and their adherence to return-to-play guidance. Athletes, their teammates, and, in some cases, coaches and parents may not fully appreciate the health threats posed by concussions. Similarly, military recruits are immersed in a culture that includes devotion to duty and service before self, and the critical nature of concussions may often go unheeded. According to Sports-Related Concussions in Youth, if the youth sports community can adopt the belief that concussions are serious injuries and emphasize care for players with concussions until they are fully recovered, then the culture in which these athletes perform and compete will become much safer. Improving understanding of the extent, causes, effects, and prevention of sports-related concussions is vitally important for the health and well-being of youth athletes. The findings and recommendations in this report set a direction for research to reach this goal.
Keywords: Health and Medicine

New Directions in Child Abuse and Neglect Research - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Each year, child protective services receive reports of child abuse and neglect involving six million children, and many more go unreported. The long-term human and fiscal consequences of child abuse and neglect are not relegated to the victims themselves—they also impact their families, future relationships, and society. In 1993, the National Research Council (NRC) issued the report, Under-standing Child Abuse and Neglect, which provided an overview of the research on child abuse and neglect. New Directions in Child Abuse and Neglect Research updates the 1993 report and provides new recommendations to respond to this public health challenge. According to this report, while there has been great progress in child abuse and neglect research, a coordinated, national research infrastructure with high-level federal support needs to be established and implemented immediately. New Directions in Child Abuse and Neglect Research recommends an actionable framework to guide and support future child abuse and neglect research. This report calls for a comprehensive, multidisciplinary approach to child abuse and neglect research that examines factors related to both children and adults across physical, mental, and behavioral health domains—including those in child welfare, economic support, criminal justice, education, and health care systems—and assesses the needs of a variety of subpopulations. It should also clarify the causal pathways related to child abuse and neglect and, more importantly, assess efforts to interrupt these pathways. New Directions in Child Abuse and Neglect Research identifies four areas to look to in developing a coordinated research enterprise: a national strategic plan, a national surveillance system, a new generation of researchers, and changes in the federal and state programmatic and policy response.
Keywords: Behavioral and Social Sciences; Health and Medicine

Improving Access to Oral Health Care for Vulnerable and Underserved Populations - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Access to oral health care is essential to promoting and maintaining overall health and well-being, yet only half of the population visits a dentist each year. Poor and minority children are less likely to have access to oral health care than are their nonpoor and nonminority peers. Older adults, people who live in rural areas, and disabled individuals, uniformly confront access barriers, regardless of their financial resources. The consequences of these disparities in access to oral health care can lead to a number of conditions including malnutrition, childhood speech problems, infections, diabetes, heart disease, and premature births. Improving Access to Oral Health Care for Vulnerable and Underserved Populations examines the scope and consequences of inadequate access to oral health services in the United States and recommends ways to combat the economic, structural, geographic, and cultural factors that prevent access to regular, quality care. The report suggests changing funding and reimbursement for dental care; expanding the oral health work force by training doctors, nurses, and other nondental professionals to recognize risk for oral diseases; and revamping regulatory, educational, and administrative practices. It also recommends changes to incorporate oral health care into overall health care. These recommendations support the creation of a diverse workforce that is competent, compensated, and authorized to serve vulnerable and underserved populations across the life cycle. The recommendations provided in Improving Access to Oral Health Care for Vulnerable and Underserved Populations will help direct the efforts of federal, state, and local government agencies; policy makers; health professionals in all fields; private and public health organizations; licensing and accreditation bodies; educational institutions; health care researchers; and philanthropic and advocacy organizations.
Keywords: Health and Medicine

Educating Children with Autism - National Research Council (The National Academies Press, 2001)
Autism is a word most of us are familiar with. But do we really know what it means? Children with autism are challenged by the most essential human behaviors. They have difficulty interacting with other people—often failing to see people as people rather than simply objects in their environment. They cannot easily communicate ideas and feelings, have great trouble imagining what others think or feel, and in some cases spend their lives speechless. They frequently find it hard to make friends or even bond with family members. Their behavior can seem bizarre. Education is the primary form of treatment for this mysterious condition. This means that we place important responsibilities on schools, teachers and children's parents, as well as the other professionals who work with children with autism. With the passage of the Individuals with Disabilities Education Act of 1975, we accepted responsibility for educating children who face special challenges like autism. While we have since amassed a substantial body of research, researchers have not adequately communicated with one another, and their findings have not been integrated into a proven curriculum. Educating Children with Autism outlines an interdisciplinary approach to education for children with autism. The committee explores what makes education effective for the child with autism and identifies specific characteristics of programs that work. Recommendations are offered for choosing educational content and strategies, introducing interaction with other children, and other key areas. This book examines some fundamental issues, including: How children's specific diagnoses should affect educational assessment and planning How we can support the families of children with autism Features of effective instructional and comprehensive programs and strategies How we can better prepare teachers, school staffs, professionals, and parents to educate children with autism What policies at the federal, state, and local levels will best ensure appropriate education, examining strategies and resources needed to address the rights of children with autism to appropriate education. Children with autism present educators with one of their most difficult challenges. Through a comprehensive examination of the scientific knowledge underlying educational practices, programs, and strategies, Educating Children with Autism presents valuable information for parents, administrators, advocates, researchers, and policy makers.
Keywords: Health and Medicine

Community Programs to Promote Youth Development - National Research Council; Institute of Medicine (The National Academies Press, 2002)
After-school programs, scout groups, community service activities, religious youth groups, and other community-based activities have long been thought to play a key role in the lives of adolescents. But what do we know about the role of such programs for today's adolescents? How can we ensure that programs are designed to successfully meet young people's developmental needs and help them become healthy, happy, and productive adults? Community Programs to Promote Youth Development explores these questions, focusing on essential elements of adolescent well-being and healthy development. It offers recommendations for policy, practice, and research to ensure that programs are well designed to meet young people's developmental needs. The book also discusses the features of programs that can contribute to a successful transition from adolescence to adulthood. It examines what we know about the current landscape of youth development programs for America's youth, as well as how these programs are meeting their diverse needs. Recognizing the importance of adolescence as a period of transition to adulthood, Community Programs to Promote Youth Development offers authoritative guidance to policy makers, practitioners, researchers, and other key stakeholders on the role of youth development programs to promote the healthy development and well-being of the nation's youth.
Keywords: Behavioral and Social Sciences; Health and Medicine

Investing in the Health and Well-Being of Young Adults - Institute of Medicine; National Research Council (The National Academies Press, 2015)
Young adulthood - ages approximately 18 to 26 - is a critical period of development with long-lasting implications for a person's economic security, health and well-being. Young adults are key contributors to the nation's workforce and military services and, since many are parents, to the healthy development of the next generation. Although 'millennials' have received attention in the popular media in recent years, young adults are too rarely treated as a distinct population in policy, programs, and research. Instead, they are often grouped with adolescents or, more often, with all adults. Currently, the nation is experiencing economic restructuring, widening inequality, a rapidly rising ratio of older adults, and an increasingly diverse population. The possible transformative effects of these features make focus on young adults especially important. A systematic approach to understanding and responding to the unique circumstances and needs of today's young adults can help to pave the way to a more productive and equitable tomorrow for young adults in particular and our society at large. Investing in The Health and Well-Being of Young Adults describes what is meant by the term young adulthood, who young adults are, what they are doing, and what they need. This study recommends actions that nonprofit programs and federal, state, and local agencies can take to help young adults make a successful transition from adolescence to adulthood. According to this report, young adults should be considered as a separate group from adolescents and older adults. Investing in The Health and Well-Being of Young Adults makes the case that increased efforts to improve high school and college graduate rates and education and workforce development systems that are more closely tied to high-demand economic sectors will help this age group achieve greater opportunity and success. The report also discusses the health status of young adults and makes recommendations to develop evidence-based practices for young adults for medical and behavioral health, including preventions. What happens during the young adult years has profound implications for the rest of the life course, and the stability and progress of society at large depends on how any cohort of young adults fares as a whole. Investing in The Health and Well-Being of Young Adults will provide a roadmap to improving outcomes for this age group as they transition from adolescence to adulthood.
Keywords: Health and Medicine; Behavioral and Social Sciences

Weight Gain During Pregnancy: Reexamining the Guidelines - Institute of Medicine; National Research Council (The National Academies Press, 2009)
As women of childbearing age have become heavier, the trade-off between maternal and child health created by variation in gestational weight gain has become more difficult to reconcile. Weight Gain During Pregnancy responds to the need for a reexamination of the 1990 Institute of Medicine guidelines for weight gain during pregnancy. It builds on the conceptual framework that underscored the 1990 weight gain guidelines and addresses the need to update them through a comprehensive review of the literature and independent analyses of existing databases. The book explores relationships between weight gain during pregnancy and a variety of factors (e.g., the mother's weight and height before pregnancy) and places this in the context of the health of the infant and the mother, presenting specific, updated target ranges for weight gain during pregnancy and guidelines for proper measurement. New features of this book include a specific range of recommended gain for obese women. Weight Gain During Pregnancy is intended to assist practitioners who care for women of childbearing age, policy makers, educators, researchers, and the pregnant women themselves to understand the role of gestational weight gain and to provide them with the tools needed to promote optimal pregnancy outcomes.
Keywords: Health and Medicine; Food and Nutrition

The Promise of Adolescence: Realizing Opportunity for All Youth - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Adolescence—beginning with the onset of puberty and ending in the mid-20s—is a critical period of development during which key areas of the brain mature and develop. These changes in brain structure, function, and connectivity mark adolescence as a period of opportunity to discover new vistas, to form relationships with peers and adults, and to explore one's developing identity. It is also a period of resilience that can ameliorate childhood setbacks and set the stage for a thriving trajectory over the life course. Because adolescents comprise nearly one-fourth of the entire U.S. population, the nation needs policies and practices that will better leverage these developmental opportunities to harness the promise of adolescence—rather than focusing myopically on containing its risks. This report examines the neurobiological and socio-behavioral science of adolescent development and outlines how this knowledge can be applied, both to promote adolescent well-being, resilience, and development, and to rectify structural barriers and inequalities in opportunity, enabling all adolescents to flourish.
Keywords: Behavioral and Social Sciences; Health and Medicine